Evaluation of Local Supplemental Food Program for Undernourished Toddlers - Ramadhania , Salsabila; Endah Mulyani; Eka Srirahayu Ariestiningsih (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Undernutrition among toddlers is a major public health issue in Indonesia, as it directly affects children's physical growth, cognitive development, and quality of life in the future. This study aims to evaluate the effectiveness of a Supplementary Feeding Program (PMT) using locally sourced food ingredients as a form of nutritional intervention for undernourished toddlers in the working area of Puskesmas Nelayan, Gresik Regency. A quantitative research design with an analytic experimental approach was applied. The study involved 56 toddlers aged 15–56 months who were identified as undernourished based on the weight-for-age (W/A) indicator. The intervention lasted for 56 days and included a five-day cycle menu composed of staple foods and snacks made from local ingredients rich in carbohydrates, animal and plant-based proteins, vitamins, and minerals. The intervention was closely monitored by nutritionists, midwives, and community health volunteers. Statistical analysis using a paired sample t-test showed a significant change in Z-scores before and after the intervention (p = 0.000), indicating that the locally based PMT was effective in improving the nutritional status of the toddlers. In addition to weight gain, the program also enhanced parental knowledge about balanced nutrition and the use of local food ingredients in daily menu planning. Thus, the PMT program not only had a physical impact on toddlers but also served as an educational tool that empowered families to adopt healthy eating habits sustainably at home.